DEPDC5 Variants Associated Malformations of Cortical Development and Focal Epilepsy With Febrile Seizure Plus/Febrile Seizures: The Role of Molecular Sub-Regional Effect - Liu, Liu; Chen, Zi-Rong; Xu, Hai-Qing; Liu, De-Tian; Mao, Yong; Liu, Han-Kui; Liu, Xiao-Rong; Zhou, Peng; Lin, Si-Mei; Li, Bin; He, Na; Su, Tao; et al. (Frontiers in Neuroscience, 2020)
To explore the phenotype spectrum of DEPDC5 variants and the possible mechanisms underlying phenotypical variation, we performed targeted next-generation sequencing in 305 patients with focal epilepsies and 91 patients with generalized epilepsies. Protein modeling was performed to predict the effects of missense mutations. All previously reported epilepsy-related DEPDC5 variants were reviewed. The genotype-phenotype correlations with molecular sub-regional implications were analyzed. We identified a homozygous DEPDC5 mutation (p.Pro1031His) in a case with focal cortical dysplasia and eight heterozygous mutations in 11 families with mild focal epilepsies, including 13 patients in eight families with focal epilepsy with febrile seizures plus/febrile seizures (FEFS+/FS). The mutations included one termination codon mutation (p.Ser1601_Ter1604del_ext133), three truncating mutations (p.Val151Serfs*27, p.Arg239*, and p.Arg838*), and four missense mutations (p.Tyr7Cys, p.Tyr836Cys, p.Pro1031His, and p.Gly1545Ser) that were predicted to affect hydrogen bonds and protein stability. Analysis on epilepsy-related DEPDC5 variants revealed that malformations of cortical development (MCD) had a tendency of higher frequency of null mutations than those without MCD. MCD-associated heterozygous missense mutations were clustered in SABA domain and close to the binding sites to NPRL2/NPRL3 complex, whereas those associated with FEFS+/FS were a distance away from the binding sites. Evidence from four aspects and one possible evidence from sub-regional implication suggested MCD and FEFS+/FS as phenotypes of DEPDC5 variants. This study suggested that the phenotypes of DEPDC5 variants vary from mild FEFS+/FS to severe MCD. Heterozygous DEPDC5 mutations are generally less pathogenic and commonly associated with mild phenotypes. Bi-allelic mutations, second-hit of somatic mutations, together with the genotype-phenotype correlation and sub-regional implication of DEPDC5 variants explains severe phenotypes.